ANALISIS PREVALENSI LOW BACK PAIN PADA PERAWAT DI DUNIA : LITERATURE REVIEW - Astuti, Martha Sri (JPK : Jurnal Penelitian Kesehatan, 2022)
Low Back Pain (LBP) is a condition presenting sustain pain in area between waist and gluteal fold. The prime cause of LBP is ergonomic position. Nurse does a lot of bending, twisting, lifting patients or in a certain position for along time. This positions are ergonomically bad. Some interventions are done on researches gave positive result for one year. On another hand prevalence of LBP on nurses in the world is not changing for 12 years (2008-2019), between 50-70%. This prevalence is consistent whether in the poor countries, developing countries or developed countries. Psychological factors, deficiency of health allied sources and time management of the health human resource also interference the LBP prevalence on nurses. It is need to do ergonomic intervention and time human management for nurses in the workplace to know its efficiency towards decreasing LBP prevalence